WHEN ISLAMIC COSMOPOLITANISM MEET SOCIAL MEDIA TECHNOLOGY: ONLINE/ OFFLINE COMMUNITY, AUTHORITY, AND TRADITION - Supriansyah, Supriansyah (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstract: This article examines the broadcasting of religious activities via social media accounts